Growth of the maternal intestine during reproduction - Ameku, Tomotsune; Laddach, Anna; Beckwith, Hannah; Milona, Alexandra; Rogers, Loranzie S; Schwayer, Cornelia; Nye, Emma; Tough, Iain R; Thoumas, Jean-Louis; Gautam, Umesh Kumar; Wang, Yi-Fang; Jha, Shreya; et al. (Cell, 2025)
The organs of many female animals are remodeled by reproduction. Using the mouse intestine, a striking and tractable model of organ resizing, we find that reproductive remodeling is anticipatory and distinct from diet- or microbiota-induced resizing. Reproductive remodeling involves partially irreversible elongation of the small intestine and fully reversible growth of its epithelial villi, associated with an expansion of isthmus progenitors and accelerated enterocyte migration. We identify induction of the SGLT3a transporter in a subset of enterocytes as an early reproductive hallmark. Electrophysiological and genetic interrogations indicate that SGLT3a does not sustain digestive functions or enterocyte health; rather, it detects protons and sodium to extrinsically support the expansion of adjacent Fgfbp1-positive isthmus progenitors, promoting villus growth. Our findings reveal unanticipated specificity to physiological organ remodeling. We suggest that organ- and state-specific growth programs could be leveraged to improve pregnancy outcomes or prevent maladaptive consequences of such growth.
Keywords: enterocyty; Reproduction; Pregnancy; rozmnožování; střeva; reproduction; Intestines; Female; střevní sliznice; tenké střevo; zvířata; small intestine; myši; myši inbrední C57BL; Mice; SGLT3a; plasticity; Intestine, Small; intestinal epithelium; ženské pohlaví; pohyb buněk; isthmus progenitor; pregnancy; Enterocytes; Mice, Inbred C57BL; těhotenství; Cell Movement; Fgfbp1; Animals; adult organ remodeling; lactation; Intestinal Mucosa